Possible correspondences between church growth principles and nine Chinese churches in Metro Manila - Hintay, Jadaza M. ([n.p.] Adventist International Institute of advance Studies Theological Seminary, 2008)
Several attempts by the Central Luzon Conference of Seven-day Adventists to increase the number of members at the Manila Chinese SDA church have not met with success over the years. In contrast, nine Chinese churches in Metro Manila have exhibited excellent growth.
A project presented in partial fulfillment of the requirements for the degree Doctor of Ministry
Thesis (D. M.)- Adventist International Institute of Advanced Studies Theological Seminary